Does the Adverse Announcement Effect of Climate Policy Matter? - A Dynamic General Equilibrium Analysis - Marie-Catherine Riekhof; Johannes Bröcker (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
We consider a carbon emissions tax announced today, but implemented after a known time-lag. Before implementation, the announcement induces higher emissions than without intervention. In welfare terms, this adverse announcement effect could more than outweigh the gain after tax implementation. We quantify a `critical lag' such that a shorter (longer) implementation lag is a welfare gain (loss) over nointervention. We identify resource scarcity as the main driver for a short critical lag. The model is a global Ramsey Model extended by an exhaustible carbon resource and linked to a climate model.
Keywords: E21; E32; F44; G21; G28; 330; Climate Policy; Announcement Effect; Dynamic General Equilibrium; Non-renewable Resource; Backstop; Green Paradox; Welfare Evaluation; Klimapolitik; Ökosteuer; Ankündigungseffekt; Erschöpfbare Ressourcen; Wohlfahrtsanalyse; Dynamisches Gleichgewicht; Optimale Besteuerung; Theorie